Quackgrass (Elytrigia repens) control in potatoes (Solanum tuberosum) with clethodim - Ivany, Jerry; Sanderson, J. (Phytoprotection, 2003)
SummaryPotato growers require effective control of quackgrass (Elytrigia repens) so as to obtain maximum yield. We examined the effect of different quackgrass growth parameters on effectiveness of clethodim and compared clethodim to selected herbicides. Reduction of the initial top growth of quackgrass with clethodim applied at the five-leaf stage was less than at the three-leaf stage at all rates of application. Shoot regrowth and rhizome production occurred at rates of application from 0.075 to 0.150 kg a.i. ha-1 but only to a very minor level at the highest rate of 0.240 kg a.i. ha-1 at either stage of application. Control was not affected by rhizome length with equal reduction in initial growth, regrowth, and rhizome weight obtained on plants grown from two-node and ten-node rhizome pieces at rates of 0.120 kg a.i. ha-1 or higher. Removal of quackgrass shoots 6 hours after treatment resulted in increased regrowth and rhizome weight at all application rates but the response was progressively overcome by increasing the rate of application.The removal of quackgrass shoots 24 or 96 hours after treatment had no adverse effect on reduction in quackgrass growth indicating rapid clethodim translocation in the greenhouse. In the field, clethodim provided greater than 80% control of quackgrass at the three to four-leaf stage with 0.150 kg a.i. ha-1 when used in combination with ammonium sulphate.